1987
DOI: 10.1161/01.cir.75.2.482
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of exercise-induced myocardial ischemia in dogs with recruitment of coronary vasodilator reserve by nifedipine.

Abstract: 482-490, 1987. RECENT STUDIES indicate that the long-held concept of maximum coronary vasodilation during myocardial ischemia is not correct. Experiments on regional myocardial blood flow in anesthetized dogs' 2 and pigs3 with significant ischemia at rest have shown that at coronary perfusion pressures as low as 35 mm Hg, associated with a marked reduction of myocardial blood flow, vasodilator reserve remained, i.e., intracoronary infusion of adenosine increased myocardial blood flow. However, the effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Larger, controlled trials looking at the effect of ␣-blockade in patients with chronic stable angina are lacking and are probably worthwhile only with agents that do not block presynaptic ␣ 2 -adrenoceptors and thus do not increase norepinephrine release but are nevertheless effective at postsynaptic ␣ 2 -adrenoceptors, which appear more important than ␣ 1 -adrenoceptors in mediating ␣-adrenergic coronary vasoconstriction. Such requirements are well met by calcium antagonists that may counteract ␣-adrenergic coronary constriction in both the experimental 64 and clinical setting. 65 …”
Section: ␣-Adrenergic Coronary Vasoconstriction During Interventionsmentioning
confidence: 99%
“…Larger, controlled trials looking at the effect of ␣-blockade in patients with chronic stable angina are lacking and are probably worthwhile only with agents that do not block presynaptic ␣ 2 -adrenoceptors and thus do not increase norepinephrine release but are nevertheless effective at postsynaptic ␣ 2 -adrenoceptors, which appear more important than ␣ 1 -adrenoceptors in mediating ␣-adrenergic coronary vasoconstriction. Such requirements are well met by calcium antagonists that may counteract ␣-adrenergic coronary constriction in both the experimental 64 and clinical setting. 65 …”
Section: ␣-Adrenergic Coronary Vasoconstriction During Interventionsmentioning
confidence: 99%
“…This is not necessarily a disadvantage: Because the coronary reserve distal to a severe stenosis on a coronary artery is already exhausted [37], calcium-channel blockers will particularly dilate intact coronary arteries, thus inducing a flow redistribution and "stealing" blood flow from the ischemic region [30]. This latter property was challenged after it had been demonstrated that calciumchannel blockers could also preferentially increase ischemic subendocardial blood flow [38].…”
Section: Effect On Myocardial Oxygen Demand-supply Balancementioning
confidence: 99%
“…Whereas some vasodilating drugs (e.g., dipyridamole, chromo,mr) are prone to induce a coronary steal phenomenon [33,34], calcium antagonists such as nifedipine increase blood supply to both the uncompromised myocardium and the poststenotic ischemic regions [35,36]. In clogs, nisoldipine enhanced coronary collateral flow to poststenotic regions with a comparable distribution to the epicardial and endocardial layers [37 I.…”
Section: Discussionmentioning
confidence: 99%